2018
DOI: 10.29252/jrdms.3.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Prevalence of Systemic Diseases in Patients Referring to the Oral and Maxillofacial Medicine Department of the Dental Branch of Islamic Azad University of Tehran During 2016-17

Abstract: Background and Aim:Given the relatively high prevalence of systemic diseases, the importance of these diseases in patient management, treatment planning, and treatment outcomes, the controversy in the reported incidence rates, and changes in the frequency of diseases over time, we aimed to determine the prevalence of systemic diseases among the patients referring to the Dental Branch of Islamic Azad University of Tehran in 2016-17. Materials and Methods: : The present research was carried out by studying the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 9 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…The mean age of dental patients with comorbidities was similar to other studies published prior to the current pandemic, indicating that co-morbidities mainly affected the middle-aged and elderly (only one study showed the lack of any relationship between a pre-existing medical condition and age among dental school patients and may be considered to be exceptional) [ 7 , 12 , 14 - 15 ]. The incidence of chronic diseases is increasing worldwide due to an aging population and changing lifestyles.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The mean age of dental patients with comorbidities was similar to other studies published prior to the current pandemic, indicating that co-morbidities mainly affected the middle-aged and elderly (only one study showed the lack of any relationship between a pre-existing medical condition and age among dental school patients and may be considered to be exceptional) [ 7 , 12 , 14 - 15 ]. The incidence of chronic diseases is increasing worldwide due to an aging population and changing lifestyles.…”
Section: Discussionsupporting
confidence: 79%
“…Except for one study [ 7 ], most studies suggest that a greater proportion of patients who applied to the dental outpatient clinic in the pre-pandemic period were females [ 8 , 11 - 12 , 15 ]. Supporting these data, the current study also found that predominantly female patients, both with and without comorbidities, visited dental clinics during the pandemic period as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of comorbid conditions in patients presenting with diseases of the oral cavity is not much studied as our population is concerned as only a few studies are available. 5 However, international literature showed high prevalence; [6][7] apart from this, a high prevalence of systemic diseases like hypertension and diabetes in our community warrants screening of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Dental management are widely influenced by systemic diseases and medications, and dental treatments may have effects on the systemic diseases of the patients. 4,5 The prevalence of systemic diseases among dental patients in different studies conducted in Tehran, Mashhad, India, and Saudi Arabia has been reported to be 10.3% to 52.8% [6][7][8][9] and Diabetes mellitus, hypertension, and digestive disorders were among the prevalent systemic diseases in dental patients.…”
Section: Introductionmentioning
confidence: 99%